2021
DOI: 10.1038/s12276-021-00680-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting single-cell genomes through the clonal organoid technique

Abstract: The revolution in genome sequencing technologies has enabled the comprehensive detection of genomic variations in human cells, including inherited germline polymorphisms, de novo mutations, and postzygotic mutations. When these technologies are combined with techniques for isolating and expanding single-cell DNA, the landscape of somatic mosaicism in an individual body can be systematically revealed at a single-cell resolution. Here, we summarize three strategies (whole-genome amplification, microdissection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 115 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…SVs, and particularly complex SVs, play a significant yet underappreciated role in determining how cancer genomes evolve. Single-cell WGS applied to organoid systems [126,127] has enabled high-resolution phylogenetic studies and functional interrogation of subclonal SVs [128]. In addition, longitudinal single-cell WGS of patient-derived xenografts from tumour samples has demonstrated that CNAs have an underappreciated impact on clonal fitness [129].…”
Section: Structural Variation As a Critical Dimension In Tumour Evolu...mentioning
confidence: 99%
“…SVs, and particularly complex SVs, play a significant yet underappreciated role in determining how cancer genomes evolve. Single-cell WGS applied to organoid systems [126,127] has enabled high-resolution phylogenetic studies and functional interrogation of subclonal SVs [128]. In addition, longitudinal single-cell WGS of patient-derived xenografts from tumour samples has demonstrated that CNAs have an underappreciated impact on clonal fitness [129].…”
Section: Structural Variation As a Critical Dimension In Tumour Evolu...mentioning
confidence: 99%
“…Our approaches allowed for the sensitive and precise investigation soL1Rs in single genomes with minimal amplification and dropout artifacts that frequently occur in whole-genome amplification (WGA)-based single-genome sequencing 28 and in laser capture microdissection (LCM)-based clonal patch sequencing ( Supplementary Discussion ). In addition, our approach enabled us to combine DNA methylation and gene expression profiles from the same clones, which are challenging in other approaches 29 . Furthermore, by integrating early developmental lineages of clones reconstructed by somatic mutations as cellular barcodes 8 , the early molecular dynamics of the mutational, transcriptional, and epigenetic profiles of L1s were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In between both approaches, MALBAC starts with an isothermal preamplification followed by PCR amplification. An important caveat of these techniques is the mutation rate, up to 1–40 mutations per 100 kb [ 4 ], which needs to be considered in the variant calling process and subsequent analyses. Primary template-directed amplification (PTA) is an improved alternative that takes advantage of the low error rate of the polymerase used in MDA with some modifications in the amplification [ 5 ].…”
Section: Somatic Variant Detectionmentioning
confidence: 99%
“…Induced pluripotent stem cell (iPSC) culture is another option. However, the culture conditions and environmental agents can be a selective bottleneck to a group of cells and can induce de novo mutations during culture [ 4 ]. In contrast, organoid culture technologies have the advantage of being compatible with multiple human cell types, and long-term genome-stable cultures can be obtained.…”
Section: Somatic Variant Detectionmentioning
confidence: 99%